Fiscal aspects of soft drugs legalization. Experience from the United States of America - Tim, Artur (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
Over the last few years there has been noticed a change in the approach of the federal administration of the United States of America to the issue of marijuana. There has been done a shift from war absorbing many victims to leaving a decision on legalizing marijuana actually up to the individual states. The Author describes that process, presents controversies caused by a breakthrough judgment in the case of Gonzales v. Reich, analyses a status of lawyers from the drug industry (called “marijuana lawyers”), indicates a tax planning process in the aspect of marijuana trade and shows the scale of gain received by the public structures due to imposing turnover taxes on using marijuana and income taxes on dealers and entities cooperating with them.